2022
DOI: 10.15616/bsl.2022.28.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Chemical Components of Hydrolysate from Silkworm Fed with Cudrania tricuspidata Leaves

Abstract: The purpose of this study was to develop hydrolysate from silkworm (Cudrania Silkworm Fibroin Peptide; CSFP), a food containing components for improving blood vessel health. In general, Cudrania tricuspidata leaves contain about 5 times more rutin and 25 times more dihydroquercetin than mulberry leaves. 1-Deoxynojirimycine (1-DNJ), dihydroquercetin and rutin inhibit the activity of carbohydrate-digesting enzymes, inhibit blood lipid peroxidation, and regulate insulin secretion, which helps blood vessels to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…The polyphenol content of ESLC extracts developed using enzymatic treatment was remarkably higher than that of SLC (p < 0.05). This was similar to the findings of Choi et al [21], who reported that the…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The polyphenol content of ESLC extracts developed using enzymatic treatment was remarkably higher than that of SLC (p < 0.05). This was similar to the findings of Choi et al [21], who reported that the…”
Section: Discussionsupporting
confidence: 93%
“…The nutritional and functional components of mulberry leaves significantly affect silkworm growth and quality [19]. Cudrania tricuspidata belongs to the family Moraceae, and compared to ordinary mulberry leaves, the leaves are rich in functional components and bioactive substances such as gamma-aminobutyric acid, rutin, dihydroquercetin, and 1-deoxynojirimycin [20,21]. Particularly, it has been reported to have excellent antioxidant activity and neuroprotective effects owing to its high bioactive substance content, such as polyphenols and flavonoids [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Cudrania tricuspidata (commonly called mandarin melon berry, silkworm thorn, etc.) belongs to the family Moraceae, and its leaves are rich in bioactive substances and possess excellent antioxidant activity compared to Morus alba [30][31][32], especially the content of the neurotransmitter gamma-aminobutyric acid, which has been reported to be effective in improving memory [33]. However, there are no studies on the functional effects of silkworms that are fed Cudrania tricuspidata leaves.…”
Section: Introductionmentioning
confidence: 99%